Formula covering black holes and the industrial sample negative germ - Alvandi, Rezvan (International Journal of Scientific Research and Management (IJSRM), 2023)
The main purpose of this study is to discuss the ways of neutralizing the resultant forces on the spacecraft in the black hole so that they can be equal to zero.  Based on Einstein's relativity theory*, the intensity of the gravity force reduces the speed of the mass. But we all know that this formula is not true about black holes, since black holes' high gravity absorbs everything, including light. However, the issue of space craft’s passing through black holes with the speed of light is still debatable, although the required formula has not been discovered yet. In this paper, it has been attempted to discuss the ways of discovering the formula for calculating the forces imposed on the spacecraft and ways of neutralizing these forces, so that the spacecraft can successfully pass through the black holes. First, we tried to use the singularity to find the next location of the spacecraft's appearance. Then, we discussed how to produce the laboratory sample of negative germ to neutralize the resultant forces on the spacecraft.